Non-Contact Respiration Measurement during Exercise Tolerance Test by Using Kinect Sensor - Hirooki Aoki; Hidetoshi Nakamura (MDPI AG, 2018)
This study aims to assess non-contact respiration measurement during the exercise stress test using an upright bicycle ergometer and to evaluate the ventilation threshold value. We propose the tracking of the chest and abdomen by applying the motion capture function of the Kinect V2 sensor to cope with an increase in physical exercise accompanied by an increase in exercise intensity. In the proposed method, the region enclosed by the four joints corresponding to the left and right shoulders and the right and left hip extracted using the Kinect sensor is set as the region of interest. The region is updated in response to changes in body movements. By extracting the signal of the pedaling frequency component from the time series data of the volume in the region, only the volume change due to respiration was extracted. The point at which the increased rate of the volume change elevates is estimated as the ventilation threshold. The assessment of the efficacy of the proposed method by comparative analysis using an expiration gas analyzer confirmed that non-contact respiration evaluation is possible with an exercise intensity of about 160 W. Furthermore, the ventilation threshold estimated by the proposed method is ±10 W of the estimated value by expiratory gas analyzer.